2019
DOI: 10.1021/acscatal.8b05171
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of PET: Current Status and Application Aspects

Abstract: Most petroleum-derived plastics, as exemplified by poly­(ethylene terephthalate) (PET), are chemically inactive and highly resistant to microbial attack. The accumulation of plastic waste results in environmental pollution and threatens ecosystems, referred to as the “microplastic issue”. Recently, PET hydrolytic enzymes (PHEs) have been identified and we reported PET degradation by a microbial consortium and its bacterial resident, Ideonella sakaiensis. Bioremediation may thus provide an alternative solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
341
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 457 publications
(352 citation statements)
references
References 97 publications
4
341
0
7
Order By: Relevance
“…PETase and MHETase catalyze similar reactions in different locations. Extracellular PETase hydrolyzes PET into MHET, which is transported into the periplasmic space of I. sakaiensis where outer membrane‐anchored MHETase hydrolyzes MHET into TPA and EG . This combination and arrangement of enzymes for metabolizing PET has so far not been found in any other organisms with fully sequenced genomes.…”
Section: Pet and Its Recyclingmentioning
confidence: 97%
See 2 more Smart Citations
“…PETase and MHETase catalyze similar reactions in different locations. Extracellular PETase hydrolyzes PET into MHET, which is transported into the periplasmic space of I. sakaiensis where outer membrane‐anchored MHETase hydrolyzes MHET into TPA and EG . This combination and arrangement of enzymes for metabolizing PET has so far not been found in any other organisms with fully sequenced genomes.…”
Section: Pet and Its Recyclingmentioning
confidence: 97%
“…Phylogenetic tree analysis of PHEs shows that these enzymes appear in both eukaryotes and bacteria . The bacterial domain that expresses PHEs is further divided into two major branches belonging to the phyla Actinobacteria and Proteobacteria .…”
Section: Pet and Its Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of studies have reported that several microorganisms and enzymes are capable of degrading synthetic plastics. Although numerous reviews and viewpoints on the topic of biodegradation of plastic have been published, they have mainly focused on the biodegradation of a single kind of plastic, such as PE (Restrepo-Flórez et al, 2014), PS (Ho et al, 2018), PP (Arutchelvi et al, 2008), PUR (Cregut et al, 2013;Peng et al, 2018;Magnin et al, 2019c), and PET (Wei and Zimmermann, 2017a;Kawai et al, 2019;Taniguchi et al, 2019). A comprehensive review into biodegradation of all main kinds of plastic is necessary (Wei and Zimmermann, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Not content with the finite repertoire of naturally occurring enzymes, numerous research groups have concerned on the engineering of IsPETase, which has been summarized by Taniguchi recently 14 . Recently crystal structures of PET degrading enzymes allow for expedients that exploit rational design to improve the PET degradation activity [15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%